Ground surface ultralow background spectrometer: Active shielding improvements and coincidence measurements for the Gamma3 spectrometer. (August 2017) - Cagniant, A.; Delaune, O.; Réglat, M.; Douysset, G.; Gross, P.; Le Petit, G.
Abstract: The ultralow background versatile spectrometer GAMMA 3 has been optimized with the following shielding improvements: (i) optimized nitrogen injection flux of 300 L h −1, and (ii) cosmic veto configuration with 9 scintillating plates. These improvements allow a reduction of 39% of the normalized integral background count rate down to 2.7±0.2 min −1 kgGe −1 (40–2500 keV energy range). Minimum Detectable Activities when performing direct γ-ray spectrometry or γ-γ coincidence spectrometry are compared. Highlights: Cosmic veto upgrade of the Gamma 3 spectrometer, reducing by 39% its integral background count rate, is presented. Radon-free nitrogen injection at 300 L h −1 is optimal. Resulting 214 Pb peak (350 keV) count rate is lower than 1.5 h −1 . Resulting integral background count rate on the 20–2500 keV range is 3.4 min −1 /kgGe . For active atmospheric filter, coincidence measurements provided MDA from 30% to 240% lower than direct measurements.